Extended Spectrum Beta-lactamase Producing Gram Negative Bacterial Isolates from Urine of Patients Visiting Everest Hospital, Kathmandu, Nepal - Guragain, Nisha; Pradhan, Aashish; Dhungel, Binod; Banjara, Megha Raj; Rijal, Komal Raj; Ghimire, Prakash (Tribhuvan University Journal of Microbiology, 2019)
Objectives: The study was aimed to determine the prevalence of Extended Spectrum Beta Lactamase (ESBL) producing Gram negative pathogens from urine samples along with their antimicrobial resistance. Methods: This cross-sectional study was conducted from December 2015 to May 2016 at Everest Hospital, Kathmandu. Mid-stream urine samples were collected and processed for culture by standard loop streak method. Identified bacterial isolates were tested for Antibiotic Susceptibility by modified Kirby Bauer disc diffusion method and, were subjected to ESBL screening by using 30µg cefotaxime and ceftazidime. ESBL production was confirmed by combination disc method. Results: Of the three hundred urine samples, 22.7% (67/300) showed significant growth. Four different bacterial species were identified. Among the isolates, E. coli was the most common pathogen (71.64%) followed by Klebsiella pneumoniae (14.92%), Pseudomonas spp (8.95%) and Acinetobacter spp (4.48%). Altogether 92.54% (n=62) isolates were sensitive to gentamicin, 89.55% (n=60) to amikacin, and 79.10% (n=53) to nitrofurantoin. 70.10% (n=47) isolates were resistant to antibiotic ampicillin while 62.68% (n=42) were found as Multi-Drug Resistant (MDR) and 29.8% (n=20) were ESBL producers. Conclusions: The overall prevalence of MDR and ESBL among uropathogens is low in comparison to other studies though it is essential to have a regular monitoring of ESBL producing clinical isolates in laboratory practice.